Cambodia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix examines the main developments in the real sector of Cambodia since the mid-1990s. The paper describes the path of overall GDP growth since 1994, and discusses key sectoral developments and constraints that hamper further expansion of rice output and exports as well as the private sector development. The paper reviews inflation and labor market developments since 1998. It also provides a fresh look at fiscal developments in Cambodia since the early 1990s.